Patterns and Predictions of Barley yellow dwarf virus Vector Migrations in Central Europe - Jarošová, Jana; Żelazny, Wiktor Rafał; Kundu, Jiban Kumar (Plant disease, 2019)
The bird cherry-oat aphid (Rhopalosiphum padi (L.)) is one of the most detrimental pests of cereals, causing harm mainly by transmitting Barley yellow dwarf virus (BYDV). R. padi migration has been monitored since 1992 using suction traps at five sites in the Czech Republic. The count data were subjected to the following different analyses: (i) the minimum temperature thresholds for the aphids to take off were determined; (ii) a partial redundancy analysis using the minimum, average, and maximum temperatures, as well as the wind speed, the precipitation total, and past aphid migration descriptors was performed to explain the relationship between aphid occurrences and weather patterns; and (iii) three types of models from the field of machine learning were used to predict aphid occurrences. According to our findings, (i) in Central Europe, 8°C is the temperature threshold for R. padi migration unless insufficient daylight delays the take-off; (ii) weather conditions occurring roughly 9 months before R. padi migration influence the migration size; (iii) the duration of the summer migration influences the autumn migration size; and (iv) the daytime and nighttime temperatures in the autumn determine the summer peak, whereas winter frosts and precipitation influence the autumn peak.
Keywords: field crops; Aphids; Animals; Luteovirus; Česká republika; ječmen (rod); migrace zvířat; mšice; Hordeum; insecticide treatment; viruses and viroids; zvířata; Animal Migration; machine learning; weather; Czech Republic; cereals and grains